A graphene-based photo-electro-thermal metamaterial for soft fixtures with superior grasping performance - Bowen Yang; Xuanchen Dong; Wenhao Lv; Wenzhuo Liu; Mengying Lu; Zhe Liu; Tonghui Lu; Xianglin Li; Song Lv (iScience)
Summary: Soft actuators are valued for their adaptability and diverse applications but often face challenges like slow response, high activation energy, and high energy consumption. To address these issues, we developed a graphene-assembled film (GAF) via the redox method, characterized by high thermal conductivity, conductivity, and stiffness. Using GAF as a photothermal and electrothermal driver, we engineered a sandwich-structured metamaterial (SSM) by combining two polymers with vastly different thermal expansion coefficients. The SSM achieved rapid response (<5 s), low actuation energy (≤0.22 W cm⁻2 or ≤3.55 V), and large bending curvature (>0.18 mm⁻1), surpassing conventional designs in response speed (226.2% faster) and curvature (249.1% higher). This metamaterial enables soft fixtures with superior gripping capabilities and low energy consumption, handling up to eight times the object mass of traditional designs. This work highlights advances in multi-stimulus metamaterials, offering significant implications for the development of high-performance soft actuators.